How Covid-19 has exposed inequalities in the UK food system: The case of UK food and poverty [version 1; peer review: 3 approved, 2 approved with reservations] - Maddy Power; Kate E. Pickett; Katie J. Pybus; Bob Doherty (Emerald Publishing, 2020)
This article draws upon our unique perspective as academic-practitioners working in the fields of food insecurity, food systems, and inequality to comment on the empirical and ethical implications of Covid-19 for socio-economic inequalities in access to food in the UK. The Covid-19 pandemic has revealed the profound insecurity of large segments of the UK population; increased unemployment, reduced hours, and enforced self-isolation for multiple vulnerable groups is likely to lead to an increase in UK food insecurity, exacerbating diet-related health inequalities. The social and economic crisis associated with the pandemic has exposed the fragility of the system of food charity which, at present, is a key response to growing poverty. A vulnerable food system, with just-in-time supply chains, has been challenged by stockpiling. Resultant food supply issues at food banks, alongside rapidly increasing demand and reduced volunteer numbers, has undermined many food charities, especially independent food banks. In the light of this analysis, we make a series of recommendations for social security policy, 'emergency' food provision, and retailers. We call for an immediate end to the five week wait for Universal Credit and cash grants for low income households. We ask central and local government to recognise that many food aid providers are already at capacity and unable to adopt additional responsibilities. We urge supermarkets to commit to paying their employees the Real Living Wage to mitigate against food insecurity amongst their staff now and in the future. The government's -- impressive -- response to the economic crisis associated with Covid-19 has underscored a key principle: it is the government's responsibility to protect population health, to guarantee household incomes, and to safeguard the economy. Millions of households were in poverty before the pandemic, and millions more will be so unless the government continues to protect household incomes through policy change.